Combining the Water Framework Directive with Agricultural Policy Scenarios: A Multi-Objective Analysis for the Future of Irrigated Agricultural in Portugal - Pinheiro, António C. (2005)
It is clear that the successful management of water resources must take into account the influence of policies affecting the irrigated agriculture sector. Among these, the importance of the Common Agricultural Policy (CAP) and of the Water Framework Directive (WFD) is well recognised. In Portugal, more than 606,000 hectares (INE 2001b) are allocated to irrigated agriculture, which accounts for 74.8% of all water uses (INAG 2002). To study the combined effect of these policies, two irrigated regions of Portugal, Baixo Alentejo and Lezíria do Tejo, were analysed in case studies. Multi-Criteria Decision Making models (MCDM) were applied to characterise farmers’ decision-making attitudes of the main irrigated agriculture systems of these regions. The implications of environmental (WFD) and agricultural (CAP) policy change are assessed by reproducing farmers’ decision-making behaviour. Simulation results indicate that changes in these policies are conducive to substantial adjustments within the irrigated agriculture sector. This study demonstrates that the consequences of implementing the WFD are dependent both on the water price level set by the WFD and on the agricultural policy strategy in place.